DEATH WITH DIGNITY IN THE COSTA RICAN RULE OF LAW - Sánchez Astúa, Karine (2024)
This research article addresses the concept of dignified death in Costa Rican law, through jurisprudential votes that have established dignified death as a corollary of human dignity, opening the way to a brief discussion through comparative law of our current interpretation. It is consistent with the principle of dignity. The foregoing is based on the premise that in a Social State of Law, access to health must be provided respecting the self-determination of its administrators and life in an integral way, each person being able to decide not only about their life project, but also about how to deal with his death, without exceeding the will of a terminal patient.